1998
DOI: 10.1001/archotol.124.5.564
|View full text |Cite
|
Sign up to set email alerts
|

Costs of Posttreatment Surveillance for Patients With Upper Aerodigestive Tract Cancer

Abstract: Charges vary extensively across surveillance strategies, particularly if site-specific strategies are considered, although the potential benefit of more intensive, higher-cost strategies on survival or quality of life has yet to be demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 34 publications
0
24
0
1
Order By: Relevance
“…In a study analysing different strategies for the follow-up period, Virgo et al found that there were no data to demonstrate greater efficiency for higher cost strategies. 50 They recommended a minimalist approach towards follow up but also added that their analysis was not done on actual patients and prospectively studied.…”
Section: Cost-benefit Analysismentioning
confidence: 99%
“…In a study analysing different strategies for the follow-up period, Virgo et al found that there were no data to demonstrate greater efficiency for higher cost strategies. 50 They recommended a minimalist approach towards follow up but also added that their analysis was not done on actual patients and prospectively studied.…”
Section: Cost-benefit Analysismentioning
confidence: 99%
“…Regarding the importance of patient education and cancer detection in the follow-up system, there is conflicting evidence as to whether patient surveillance versus routine clinic surveillance results in a survival advantage [4,5,17,18]. Some authors claim that up to two-thirds of recurrences can be detected through increased patient self-awareness [1,4].…”
Section: Discussionmentioning
confidence: 99%
“…Posttreatment surveillance refers to the various follow-up strategies employed in the monitoring of patients following treatment for HNC.The costs of these services have also been assessed.For example,Virgo, Paniello and Johnson [53] studied the range of follow-up strategies for HNC patients treated with curative intent and their associated costs.Thirty-one different strategies were evaluated. The actual charges ranged from $US1,198 (€2,029) to $22,807 (€38,621) per patient.…”
Section: Costs Of Follow-upmentioning
confidence: 99%